Violência, poder e pobreza em Hegel (Revista Eletrônica Estudos Hegelianos, 2022)
My aim with this text is to offer an analysis of the concept of violence in Hegel’s philosophy. This concept is far from being unambiguous and is not a central topic in Hegel’s thought. Nevertheless, although its apparent problematic and secondary role, I believe this concept can help us to tackle two blind spots of Hegel’s philosophy: 1) a time previous to the foundation of the State and 2) the postrevolutionary future, that is, the contradictions emerging from modern civil society, which tend to generate potentially violent state of marginalization. While the first includes the problem of the conceptual relation between our concept and the concept of power, the second shows that there is a challenging bound between violence and poverty. Our departing point are several uncomfortable questions such as: Is violence a previous, necessary moment of power? Is the irrational the ground of the rational order of the State? Can violence contribute to the realization of a political, objective order?